Brazilian adaptation of the Woodcock-Johnson III cognitive tests - Wechsler, Solange Muglia; Nunes, Carlos Sancineto; Schelini, Patricia Waltz; Pasian, Sonia Regina [UNESP]; Homsi, Silvia Vertoni; Moretti, Lucia; Anache, Alexandra Ayach (Sage Publications Ltd, 2010)
An adaptation of the standard battery of Woodcock-Johnson III Tests of Cognitive Abilities (WJ-III) for Brazilian children and youth was investigated. The sample was composed of 1094 students (54 percent girls), ages 7-17, living in Sao Paulo state (91 percent). Items from Brazilian school books as well as from the WJ-III Spanish version (Bateria-R) were added to comprehension-knowledge tests. Brazilian words were adapted to the auditory tests according to syllabic division and stressed syllables. Items were examined through IRT and age differences through analysis of variance. Results indicated the need to remove items from all WJ-III subtests with the exception of the visual learning test. Analysis of Variance indicated significant age differences (p <= 0.001) for all tests. Thus, the importance of a Brazilian adaptation for the WJ-III was confirmed.
Keywords: adaptation; Brazil; children; intelligence; test; Woodcock-Johnson